B7-H4 correlates with clinical outcome and immunotherapeutic benefit in muscle-invasive bladder cancer. (August 2022) - Liu, Zhaopei; Jin, Kaifeng; Zeng, Han; Shao, Fei; Chang, Yuan; Wang, Yiwei; Xu, Le; Wang, Zewei; Cui, Xingang; Zhu, Yu; Xu, Jiejie
Abstract: Aim: B7-H4, a sibling to PD-L1 in B7 family, has been reported to be a novel immune checkpoint that is prevalent among non-inflamed tumors. Herein, we attempt to explore the potential of B7-H4 in survival prediction and therapeutic guidance in muscle-invasive bladder cancer (MIBC) patients. Methods: This study included 391 patients from The Cancer Genome Atlas (TCGA) database and 122 patients from Zhongshan (ZS) Hospital. The evaluation of response to PD-L1 inhibitors was based on 270 patients in IMvigor210 cohort. Kaplan–Meier survival and multivariate analyses were performed to assess clinical outcomes in three cohorts. The correlation of B7-H4 expression with immune contexture and genomic alterations was analyzed based on immunohistochemistry, Microenvironment Cell Populations-counter (MCP-counter) tool, and whole-exome sequencing. Results: MIBC patients with the high level of B7-H4 expression (B7-H4 high ) were found to possess an inferior overall and recurrence-free survival. Nonetheless, substantial clinical benefits of cisplatin-based chemotherapy and anti-PD-L1 immunotherapy were observed in these patients. After identifying a positive correlation between B7-H4 and tumor mutation burden (TMB), clinical benefits in B7-H4 high TMB high subgroup were found to be the most upon PD-L1 blockade. Further studies revealed that B7-H4 high subgroup was featured by non-inflamed immune contexture and cell cycle-related gene alterations. Conclusions: Despite adverse clinical outcomes, B7-H4 high patients possessed superior responsiveness to chemotherapy and immunotherapy. B7-H4 stratification could also synergize with TMB to pinpoint the patients who benefited most from immunotherapy. The clinical exploration of B7-H4 as a companion predictor could allow clinicians to direct proper therapeutic agents to patients. Highlights: B7-H4 expression was proved to be an adverse prognosticator in MIBC. B7-H4 high patients had prolonged survival after chemotherapy or immunotherapy. B7-H4 high TMB high patients might benefit most from PD-L1 blockade. B7-H4 correlated with non-inflamed immune contexture in MIBC.